Preparação de biochar a partir de matérias–primas alternativas e sua aplicação na adsorção de corantes - Zazycki, Maria Amélia (2019)
Contamination of natural waters has been one of the great problems of modern society. The textile and food sectors stands out especially due to the large amounts of effluents discharged into the water bodies. Thus, it is necessary the development and improvement of technologies that promote the efficient effluent treatment and are viable. In this study, biochars were produced from alternative raw materials and applied in the treatment of colored effluents. The precursor materials were pecan nutshells wastes, chitin and MDF sheets. The residues were obtained, characterized and pyrolysed, being then converted into biochars. The biochars and their precursors were characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), x–ray diffraction (XRD) and surface area analysis (BET and BJH) techniques. Finally, the adsorption of different dyes was analyzed from the kinetic, equilibrium and thermodynamic viewpoints. Characterization analyzes indicated that the biochars presented adequate characteristics for adsorption, including microporous and mesoporous structures and interesting surface area. The biochar derived from pecan nutshell residues presented a surface area of 93 m2 g–1 . The maximum adsorption capacity was about 130 mg g–1 for RR141 dye and the adsorption kinetics followed the PSO model. The chitin– derived biochar presented a surface area of 275 m2 g–1 . Adsorption kinetics was well represented by the PSO model and the maximum adsorption capacity estimated by the Liu model was 1120.8 mg g–1 for the MV dye. The biochar derived from MDF sheet residues had a surface area of 218.8 m2 g –1 . The PSO and Freundlich models were the best to represent the adsorption kinetics and isotherms, respectively. The maximum adsorption capacity was 210 mg g–1 for the FR17 dye. The results showed that promising biochars can be prepared from alternative wastes using a simple process in their preparation, being a viable alternative for dye adsorption from aqueous solutions.